Mandailing-based character education through the MERDEKA framework in Muhammadiyah schools - Hasibuan, Nikmah; Afifah, Nur; Nanda; Azelia, Cindy; Hutabarat, Anis Pitria (Indonesian Journal of Educational Development (IJED), 2025)
Character education based on local wisdom is a crucial strategy for shaping the identity and morality of the younger generation in a culturally relevant manner. This study aims to develop and evaluate a character education model grounded in Mandailing culture through an innovative approach conceptualised in the MERDEKA framework (Marsali, Mangupa, Dalihan na Tolu, Cerita Rakyat, Marsialap Ari, Gordang Sambilan, and Maronang-onang). The research employed a descriptive quantitative approach with multistage sampling, involving 100 students from three Muhammadiyah high schools in the South Tapanuli region: 50 from SMA Muhammadiyah 11 Padangsidimpuan, 25 from Mandailing Natal, and 25 from South Tapanuli. Data were collected using a validated and reliable questionnaire instrument (α = 0.842). The findings indicate a high level of internalisation of Mandailing cultural values among students, with significant regional differences based on ANOVA results (p < 0.05). The MERDEKA model is considered effective in facilitating character learning that is reflective, collaborative, and contextual. This study offers a theoretical contribution to the development of local wisdom-based character education models and provides practical recommendations for schools to implement culturally rooted character education.